Analysis of energy efficiency of cooperative MIMO schemes - Krishnan, Narayanan (Kansas State University, 2009)
Recently, user-cooperative MIMO (multi-input multi-output) systems have been generating significant interest due to their capacity/performance gains over SISO (single-input single-output) systems. In cooperative MIMO architectures, individual nodes with single antennas collaborate with each other to act as a MIMO unit. As a result, the individual node complexity associated with traditional MIMO implementations is alleviated. This feature is especially beneficial in sensor networks and cellular systems where individual node energy, size and cost are important constraints. Additionally, cooperative MIMO schemes provide all the benefits of traditional MIMO systems. In this work, we classify the cooperative MIMO systems into three different categories equivalent to classical MIMO, MISO and SIMO systems. For the three protocols, we quantify and compare the energy efficiency of Amplify-and-Forward (AF) and Decode-and-Forward (DF) schemes on a basic three node cooperative network. Total energy is calculated considering circuit energy as well as transmission energy. For AF and DF schemes, we set a target Symbol Error Probability (SEP) and evaluate the minimum transmission energy for achieving the target SEP. In this process,we first derive an approximation for SEP at high SNR. Then, we formulate the transmission energy calculation as an optimization problem subject to the target SEP and present the theoretical solution. The result is used to compare the total energy consumption of AF and DF for the three protocols. This is unlike most of the prior efforts that primarily focus on optimum allocation of limited total power to maximize the some peformance criterion. Since any wireless systems in order to operate have a set performance criterion, we intend to minimize the resources that is capable of achieving that.
Keywords: Energy Efficiency; Cooperative Wireless Communication; SIMO, MISO, MIMO Systems; Wireless Networks; Resource Utilization; Engineering, Electronics and Electrical (0544)